2023
DOI: 10.3390/ijms242015135
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Phenotypes of Progressive Supranuclear Palsy—The Differences in Interleukin Patterns

Natalia Madetko-Alster,
Dagmara Otto-Ślusarczyk,
Alicja Wiercińska-Drapało
et al.

Abstract: Progressive supranuclear palsy (PSP) is an atypical parkinsonian syndrome based on tau pathology; its clinical phenotype differs, but PSP with Richardson’s syndrome (PSP-RS) and the PSP parkinsonism predominant (PSP-P) variant remain the two most common manifestations. Neuroinflammation is involved in the course of the disease and may cause neurodegeneration. However, an up-to-date cytokine profile has not been assessed in different PSP phenotypes. This study aimed to evaluate possible differences in neuroinfl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Brodacki et al reported abnormal elevations in IL2, IL6, and TNF-α levels in PD patients, suggesting a potential link between peripheral inflammation and PD ( Brodacki et al, 2008 ). Furthermore, peripheral inflammation may be also associated with other atypical parkinsonisms and neurodegenerative diseases, including Alzheimer’s disease (AD) and PSP ( Akiyama et al, 2000 ; Madetko-Alster et al, 2023 ). However, the specific molecular mechanisms remain largely unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Brodacki et al reported abnormal elevations in IL2, IL6, and TNF-α levels in PD patients, suggesting a potential link between peripheral inflammation and PD ( Brodacki et al, 2008 ). Furthermore, peripheral inflammation may be also associated with other atypical parkinsonisms and neurodegenerative diseases, including Alzheimer’s disease (AD) and PSP ( Akiyama et al, 2000 ; Madetko-Alster et al, 2023 ). However, the specific molecular mechanisms remain largely unclear.…”
Section: Discussionmentioning
confidence: 99%
“…PSP‐P is a more favorable clinical entity in the PSP spectrum; however certain works point out that it may be a type of a slower clinical deterioration leading to the same outcome as PSP‐RS. Glial cell‐line‐derived neurotrophic factor, interleukin‐1 and Interleukin‐6 were indicated as factors possibly impacting the evolution of PSP; however, it remains unknown whether the modulation of these elements is a mechanism that may oppose the primary neurodegeneration (Alster et al., 2024 ; Madetko‐Alster et al., 2023 ). Other works evaluating possible overlaps between neurodegeneration and inflammatory mechanisms in the pathogenesis of PSP did not indicate the two major subtypes or are based on nonspecific factors as neutrophil‐to‐lymphocyte ratio (Brodacki et al., 2008 ; Inci et al., 2020 ; Nübling et al., 2017 ; Rydbirk et al., 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…The fact that decreased HRV is linked with PSP-RS and MSA, but not with PSP-P, may suggest that subtypes of PSP may be associated with different mechanisms affecting the autonomic nervous system [19]. Previous evaluations of HRV, though lacking the division into PSP subtypes, revealed ambiguous results, which could be partly caused by the small number of patients [20].…”
mentioning
confidence: 98%